GFZ contribution to the COSEISMIQ seismic network - Dahm, Torsten; Cesca, Simone; Heimann, Sebastian; Mikulla, Stefan; Milkereit, Claus (GFZ Data Services, 2021)
Abstract In the frame of the EU-project COSEISMIQ (COntrol SEISmicity and Manage Induced earthQuakes) natural and induced seismic events were monitored in Iceland. A temporary seismic network has been deployed in the Hengill geothermal region in Iceland, where the two largest geothermal power plants of the country are currently in operation. The GFZ contribution was the installation and operation of a small-scale seismic array in 2019-2021 in the vicinity of the broadband station MEI05 (ETH), in cooperation with ISOR (Iceland), ETH (Zurich) and DIAS (Dublin). This dataset is particularly valuable since a very dense network was deployed in a seismically active region where both induced and natural seismicity are occurring. For this reason, the collected COSEISMIQ-dataset can be used within a broad range of research topics in seismology ranging from the development and testing of new data analysis methods to induced seismicity and seismo-tectonics studies.